A clinico-histopathological study of lupus vulgaris: A 3 year experience at a tertiary care centre - Pai, Varadraj Vasant (Indian Dermatol Online J, 2014)
BACKGROUND: Lupus vulgaris is the most common form of cutaneous tuberculosis in adults. Lupus vulgaris is caused by hematogenous, lymphatic, or contiguous spread from elsewhere in the body. histologically it is charecterised by typical tubercles with or without caseation, surrounded by epitheloid histiocytes and multinucleate giant cells in the superficial epidermis with prominent peripheral lymphocytes. MATERIALS AND METHOD: All cases of clinically and histopathologicaly diagnosed lupus vulgaris over the previous five years were included in the study. RESULTS: Fourteen cases of lupus vulgaris cases reported during the study period with eaqual incidence among males and females. DISCUSSION: Plaque type of lupus vulgaris was the most common type. Histopathologically tubercular granulomas were seen in all cases as compared to other studies. CONCLUSION: Different patterns of lupus vulgaris are reported